2014
DOI: 10.7314/apjcp.2014.15.17.7235
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Practice of Cervical Cancer Screening among Female University Students from 25 Low, Middle Income and Emerging Economy Countries

Abstract: Cervical cancer, the third commonest cancer in women worldwide, can be prevented through early detection by cervical screening (Pap smear). The aim of this study was to investigate the attitudes and practice of cervical cancer screening among female undergraduate university students from 25 low, middle income and emerging economy countries. Using anonymous questionnaires, data were collected from 9,194 female undergraduate university students aged 18-26 years (mean age 20.9, SD=2.0) from 26 universities in 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 18 publications
3
15
0
1
Order By: Relevance
“…The individual self-assessment of health status as regular, poor or very poor may be the result of choices and adoption of unhealthy habits, such as cigarette smoking. A previous study also showed the lower adherence of smoker women to the Pap test compared to non-smokers (23) . This is a serious situation, given that smoking interferes with the incidence and prevalence of HPV infection and is associated with invasive cervical cancer (2,24) .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The individual self-assessment of health status as regular, poor or very poor may be the result of choices and adoption of unhealthy habits, such as cigarette smoking. A previous study also showed the lower adherence of smoker women to the Pap test compared to non-smokers (23) . This is a serious situation, given that smoking interferes with the incidence and prevalence of HPV infection and is associated with invasive cervical cancer (2,24) .…”
Section: Discussionmentioning
confidence: 82%
“…This is a serious situation, given that smoking interferes with the incidence and prevalence of HPV infection and is associated with invasive cervical cancer (2,24) . Thus, individuals with less healthy habits such as lack of physical activity, unbalanced diet, and high alcohol consumption may be less likely to undergo preventive exams such as the Pap test (23) .…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 77 papers and one dissertation were eligible for analysis and were listed in the order of publication years. [171819202122232425262728293031323334353637383940414243444546474849505152535455565758596061626364656667686970717273747576777879808182838485868788899091929394] The review process is explained in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…The studies consist of different populations such as women and men from different community groups[17202425313235394143454751616669717379808586909293]And attended clinics[2729425259676872757682]Students (nursing/medical/paramedical/nonmedical)[3840464850565860646974818389]Health-care providers (doctors, nurses, and other health workers);[1828365354555657626365667778889194] migrated Indians;[1921262730333437498487] and cervical cancer patients. [23]…”
Section: Methodsmentioning
confidence: 99%
“…16 A broad survey of 9,194 women aged 18-26 years in 25 countries across Asia, Africa and the Americas, noted that the cervical cancer screening practices were considered inadequate and efforts should be made to develop programs that can increase screening for cervical cancer, 17 showing that this issue is wide ranging, requiring specific actions for change in the health promotion of women.…”
mentioning
confidence: 99%